Multiple-sprint work: Methodological, physiological, and experimental issues - Glaister, M. (International Journal of Sports Physiology and Performance, 2008)
Tests of repeated-sprint ability provide a simple way to evaluate the basic physical characteristics of speed and endurance necessary to excel in various multiple-sprint sports. Furthermore, such tests help overcome the complications associated with field-based evaluations of this type of exercise. Nevertheless, despite over 40 y of research, many issues regarding our understanding of multiple-sprint work remain unresolved. This commentary aims to raise awareness of issues relating to methodology, physiological responses, and the effectiveness of various ergogenic and training strategies; to promote a greater understanding; and to drive future research.